Whole-sky imaging - Muhammad Farid Asyraf Mohd Afandi (Nanyang Technological University, 2020)
This project revolves around the reconfiguration and improvements in the current version of the WAHRSIS 6. It serves to provide documentation on its method of configuration as well as its results from its deployment. This report will be sectioned into five parts, beginning with an introduction of Whole Sky Imagers and its relevance in different research areas, then introducing the objective of this report. The next sections will be on the descriptions of hardware and software components used and its justifications, followed by the methods and steps in configuring the components as well as explanations on them. Then, an evaluation on the observations recorded during its testing stages is done, concluded with discussing this version of the WAHRSIS 6’s limitations and possible future work that could be implemented on this version or implemented on newer versions of the WAHRSIS.